Life history and demography of Oenocarpus bataua var bataua in the Central Andean Cordillera, Colombia (2013)
Abstract: This thesis involves two papers, both accepted by Forest Ecology and Management. We model the growth in height of Oenocarpus bataua var. bataua as a function of age in premontane forest of the Central Cordillera, Colombia and the duration of the establishment phase, the spatial pattern, its vital attributes, and its demography. To do this we used 36 permanent plots censuses up to 13.4 years. The height growth model as a function on age was validated by 14C dating, the establishment phase dated by 14C lasted 37.5 ± 0.7 years. Some other results were: the structure of heights and ages in bell-shaped suggests that this population is not sustainable in the long term, the doubling time that exceeds in 8.1 years the half-life shows that this population is declining. We suggest that the clumped spatial pattern at the landscape level could be due to selective logging about which we present evidences dating back nearly 90 years ago. We suggest that groups of O. bataua were established immediately after the selective logging of trees.